Tracking Labile Copper Fluctuation In Vivo/Ex Vivo: Design and Application of a Ratiometric Near-Infrared Fluorophore Derived from 4‑Aminostyrene-Conjugated Boron Dipyrromethene - Xu, Hongxia; Yao, Shankun; Chen, Yuncong; Zhang, Changli; Zhang, Shuren; Yuan, Hao; Chen, Zhongyan; Bai, Yang; Yang, Tao; Guo, Zijian; He, Weijiang (Inorganic chemistry, 2021)
Specimen differences, tissue-dependent background fluorescence and scattering, and deviated specimen position and sensor concentration make optical imaging for labile copper fluctuation in animals questionable, and a signal comparison between specimens is infeasible. We proposed ratiometric optical imaging as an alternative to overcome these disadvantages, and a near-infrared (NIR) ratiometric sensor, BDPS1, was devised therefore by conjugating boron dipyrromethene (BODIPY) with 4-aminostyrene and modifying the 4-amino group as a Cu+ chelator. BDPS1 possessed an excitation ratiometric copper-sensing ability to show the ratio of NIR emission (710 nm) upon excitation at 600 nm to that at 660 nm, F ex600/F ex660, increasing from 2.8 to 10.7. This sensor displayed still the opposite copper response of its internal charge transfer (ICT; 670 nm) and local (581 nm) emission bands. Ratiometric imaging with this sensor disclosed a higher labile copper region near the nucleus apparatus, and HEK-293T cells were more sensitive to copper incubation than MCF-7 cells. Dual excitation ratiometric imaging with this sensor realized tracking of labile copper fluctuation in mice, and the whole-body imaging found that tail intravenous injection of CUTX-101, a therapeutical agent for Menkes disease, led to a distinct labile copper increase in the upper belly. The ex vivo imaging of the resected viscera of mice revealed that CUTX-101 injection enhanced the labile copper level in the liver, intestine, lung, and gall bladder in sequence, yet the kidney, heart, and spleen showed almost no response. This study indicated that modifying BODIPY as an extended ICT fluorophore, with its electron-donating group being derived as a metal chelator, is an effective design rationale of NIR ratiometric sensors for copper tracking in vivo/ex vivo.